Public space: narratives and desires (2013)
The basis of the article is to look at public space as the domain for communication and for satisfying “the longing for the city”, an outlook by far identifiable within the best narrators: from Pamuk to Borges, from Calvino to Auster, all storylines recognize the city as the space for existence, a space made out of places, passages and paths, persons and events. Urban life exemplify the simultaneous, the multiple and the fragmented, and literature, with its capacity to suggest images and convey emotions, depicts life’s sense through small events that become a milestone for individual memories that narrative converts into moments and places for encounters. Literary images transform memory into words and these allow the sharing of reminiscences.